Genome-wide association study identifies five loci associated with lung function. - Repapi, E; Sayers, I; Wain, L; Burton, P; Johnson, T; Obeidat, M; Zhao, J; Ramasamy, A; Zhai, G; Vitart, V; Huffman, J; Igl, W; et al. (2010)
Pulmonary function measures are heritable traits that predict morbidity and mortality and define chronic obstructive pulmonary disease (COPD). We tested genome-wide association with forced expiratory volume in 1 s (FEV(1)) and the ratio of FEV(1) to forced vital capacity (FVC) in the SpiroMeta consortium (n = 20,288 individuals of European ancestry). We conducted a meta-analysis of top signals with data from direct genotyping (n < or = 32,184 additional individuals) and in silico summary association data from the CHARGE Consortium (n = 21,209) and the Health 2000 survey (n < or = 883). We confirmed the reported locus at 4q31 and identified associations with FEV(1) or FEV(1)/FVC and common variants at five additional loci: 2q35 in TNS1 (P = 1.11 x 10(-12)), 4q24 in GSTCD (2.18 x 10(-23)), 5q33 in HTR4 (P = 4.29 x 10(-9)), 6p21 in AGER (P = 3.07 x 10(-15)) and 15q23 in THSD4 (P = 7.24 x 10(-15)). mRNA analyses showed expression of TNS1, GSTCD, AGER, HTR4 and THSD4 in human lung tissue. These associations offer mechanistic insight into pulmonary function regulation and indicate potential targets for interventions to alleviate respiratory disease.